Cognitive control networks in OCD: A resting-state connectivity study in unmedicated patients with obsessive-compulsive disorder and their unaffected relatives. (16th March 2019) - de Vries, Froukje E.; de Wit, Stella J.; van den Heuvel, Odile A.; Veltman, Dick J.; Cath, Danielle C.; van Balkom, Anton J. L. M.; van der Werf, Ysbrand D.
Abstract: Objectives: Executive network deficits are putative neurocognitive endophenotypes for obsessive-compulsive disorder (OCD). Yet, unlike alterations in fronto-striatal and limbic connectivity, connectivity in the fronto-parietal (FPN) and cingulo-opercular (CON) networks involved in cognitive control has received little attention. Methods: The coherence of FPN, CON and fronto-limbic networks was investigated in 39 unmedicated OCD patients, 16 of their unaffected siblings and 36 healthy controls using resting-state functional-connectivity MRI and a seed-based analysis approach. Results: FPN and CON connectivity was similar for patients and controls. Siblings showed higher connectivity than patients within the CON, and between the CON and FPN compared to patients and controls (trend level). In OCD patients, but not in siblings, fronto-limbic hyperconnectivity was present compared to controls. In contrast to our expectations, no group differences in resting-state connectivity of the cognitive control networks were observed between OCD patients and controls. Conclusions: The increased within- and between-network connectivity in siblings, but not in patients, could indicate a mechanism of increased cognitive control that may act as a protective mechanism. None of the observed network alterations can be considered an endophenotype for OCD since differences were present in either patients or siblings, but not in both groups.